Low-cost instrument for oscillometric blood pressure measurement - Wongjan, Anan; Julsereewong, Prasit; Julsereewong, Amphawan (My University, 2015)
This article presents a technique for design and implementation of a lowcost microcontroller-controlled instrument for noninvasive blood pressure (NIBP) measurement based on oscillometric method. The proposed measuring device consists of a HEM-CR24 cuff for wrapping around a subject’s upper arm with automatic inflation, SCX pressure sensor, pneumatic subsystem, circuitry subsystem, PIC18F452 microcontroller, and LCD display module. The systolic blood pressure (SBP), diastolic blood pressure (DBP), and heart rate (HR) can be simultaneously measured and digitally displayed. The performance of the proposed instrument is confirmed through calibration results by using the BP Pump 2 NIBP monitor tester.
Keywords: Blood pressure instrument; Diastolic blood pressure; NIBP; Oscillometric method; Systolic blood pressure